Corporate Social Responsibility Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening - Tri Nur Astuti; Mursalim Mursalim; Ummu Kalsum (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
This study aims to examine the effect of Corporate Social Responsibility (CSR) on Company Value and Profitability and how the impact of disclosure of Corporate Social Responsibility (CSR) on firm value through Profitability as an Intervening Variable. This study uses a sample of mining companies listed on the Stock Exchange and uses a purposive sampling technique. This research is quantitative. The data used is secondary data and uses data collection methods, namely documentation and literature. A study conducted using Partial Least Square (PLS) shows that Corporate Social responsibility has a negative and insignificant effect on firm value. Corporate Social responsibility has a positive and significant impact on Profitability, and Profitability has a negative and little impact on Firm Value and Profitability can mediate Corporate Social responsibility on Firm Value as an intervening variable